Influence of Welding Regimes on Structure and Properties of Steel 12KH18N10T Weld Metal in Different Spatial Positions; Metallurgist; Vol. 65, iss. 11-12 - Mamadaliev R. A. Rasul Akhmadovich; Bakhmatov P. V. Pavel Vechaslavovich; Martyushev N. V. Nikita Vladimirovich; Skeeba V. Yu. Vadim Yurjevich; Karlina A. I. Antonina Igorevna (2022, 2022)
Title screen